Genetic variants in patients with multiple arterial aneurysms - Körfer, Daniel; Grond-Ginsbach, Caspar; Peters, Andreas; Burkart, Sebastian; Hempel, Maja; Schaaf, Christian P.; Böckler, Dittmar; Erhart, Philipp (Langenbeck's archives of surgery, 2024)
Purpose: The aim of this study was to identify causal genetic variants in patients with multiple arterial aneurysms. Methods: From a total cohort of 3107 patients diagnosed with an arterial aneurysm from 2006 to 2016, patients with known hereditary connective tissue diseases, vasculitis, or other arterial pathologies (n = 918) were excluded. Of the remaining cohort (n = 2189), patients with at least 4 aneurysms at different arterial locations (n = 143) were included. Nine blood samples of respective patients were available and derived from the institutional vascular biomaterial bank, and analyzed by whole exome sequencing (WES). Possible candidate variants were selected based on in silico predictions: (I) Truncating variants or (II) Variants that were classified as likely pathogenic (SIFT score < 0.05 or PolyPhen score > 0.9) and with low (< 0.001) or unknown gnomAD allele frequency. The human genome databases GeneCards and MalaCards were used to correlate the variants with regard to possible associations with vascular diseases. Results: A total of 24 variants in 23 different genes associated with vascular diseases were detected in the cohort. One patient with eight aneurysms was heterozygous for a variant in SMAD3, for which pathogenic variants are phenotypically associated with Loeys-Dietz syndrome 3. A heterozygous variant in TNXB was found in a patient with five aneurysms. Homozygous or compound heterozygous pathogenic variants in this gene are associated with Ehlers-Danlos syndrome (classical-like). Another patient with six aneurysms carried two heterozygous TET2 variants together with a heterozygous PPM1D variant. Pathogenic variants in these genes are associated with clonal hematopoiesis of indeterminate potential (CHIP), a known risk factor for cardiovascular disease. Conclusion: All nine patients in this study carried variants in genes associated with vascular diseases. Current knowledge of the specific variants is insufficient to classify them as pathogenic at the present time, underlining the need for a better under- standing of the consequences of genetic variants. WES should be considered for patients with multiple arterial aneurysms to detect germline variants and to improve clinical management for the individual and family members.